(untitled) (Zaporizhzhia Historical Review, 2021)
During the Russian-Turkish War of 1806 ñ 1812 the Transdanube regiments are shown to have participated as a part of fighting force of the Turkish army. It was proved that a considerable number of Cossacks continued fishing in the Danube delta and resided in the pre-war area, the center of which was the village of Katyrlez.